2014
DOI: 10.1063/1.4898088
|View full text |Cite
|
Sign up to set email alerts
|

High temperature terahertz response in a p-type quantum dot-in-well photodetector

Abstract: Terahertz (THz) response observed in a p-type InAs/In0.15Ga0.85As/GaAs quantum dots-in-a-well (DWELL) photodetector is reported. This detector displays expected mid-infrared response (from ∼3 to ∼10 μm) at temperatures below ∼100 K, while strong THz responses up to ∼4.28 THz is observed at higher temperatures (∼100–130 K). Responsivity and specific detectivity at 9.2 THz (32.6 μm) under applied bias of −0.4 V at 130 K are ∼0.3 mA/W and ∼1.4 × 106 Jones, respectively. Our results demonstrate the potential use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The authors of [135] were aiming at the THz detection up to 4.28 THz (70 µm) via p-type DWELL structure operating at 130 K and above. It should be noted that most of the THz investigations thus far have been with n-type photodetectors and used dark current blocking layers [130,136] or resonant tunneling [131].…”
Section: Quantum Dots In Wellmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [135] were aiming at the THz detection up to 4.28 THz (70 µm) via p-type DWELL structure operating at 130 K and above. It should be noted that most of the THz investigations thus far have been with n-type photodetectors and used dark current blocking layers [130,136] or resonant tunneling [131].…”
Section: Quantum Dots In Wellmentioning
confidence: 99%
“…Then, using the same DWELL structure as in [135], the authors of [137] have carefully studied FIR photoresponse of the DWELL detector up to 70 µm at elevated temperatures between 100 K and 130 K. It was found that strong FIR responses can be observed at higher temperature (130 K), as it is shown in figure 13.…”
Section: Quantum Dots In Wellmentioning
confidence: 99%
“…4 During the past decade, many theoretical and experimental works about terahertz QWPs and terahertz quantum-dot detectors are carried out. [5][6][7][8][9][10][11][12][13] Due to the threedimensional confinement effects, the terahertz quantum-dot detectors can work in temperatures of more than 100 K. 11,12 The results show that such detectors become more and more promising for their potential applications in fast, integrated, and compact terahertz systems. 2 As is well known, metal grating and other periodic metal structures are widely adopted to enhance optical absorption in many detectors.…”
mentioning
confidence: 99%